Economic development and the environment : a comparison of sustainable development with conventional development economics - Mikesell, Raymond Frech (London ; New York : Mansell, 1992)
Explores the relationship between sustainable development and development economics through a combination of theoretical discussion and empirical examples. The book shows how the environment and sustainability can be integrated into development strategies.
"First published in 1992"--T.p. verso.
Includes bibliographical references and index.
oif 18/07/14
Loan
Keywords: Economic development - environmental aspects; Economic development projects; Sustainable development; Global development